Determinants of postpartum health seeking behavior in the Philippines - Abraham, Regina Pulido- (2002)
This is a retrospective cohort study which aims to determine the proportion of women who sought postpartum care exclusively for themselves and to determine the factors that influence postpartum health seeking behavior using the data on the Women's Health and Safe Motherhood-Benefit Monitoring and Evaluation Study (WHSMP-BME), 2000. It focuses on 3,519 rural reproductive women with ages 15-49 years who have at least one child and had been using a government health facility five years proceeding the survey in fifteen regions of the country. Logistic regression was used to determine the association between postpartum health seeking behavior and number of prenatal visits, complications around birth attendant, and residence in a WHSMP intervention area. The following are the results of the study: (1) fifty-five percent of women sought postpartum care exclusively for themselves, (2) women with three or more prenatal visits were more likely to seek postpartum care (OR=1.4, 95% CI=1.47, 4.19) compared to 20-35 years old women, (4) women who were attended at birth by health professionals and combination of professional and non-professional care givers were more likely to seek postpartum care, especially if they live in WHSMP intervention areas, and (5) generally, women who live in intervention areas were less likely to seek postpartum care, but if these women were attended at birth by health professionals there is a greater chance that they will seek postpartum care. Prenatal visits should be increased because there will be more opportunity to identify the health needs of the women and appropriate maternal care initiated and maintained until postpartum. Since the non-professional birth attendants are still the first line of maternal care givers in many parts of the country, they should be trained on all aspects of maternal care to include prenatal, delivery and postpartum, so that together with health professionals, a wider pool of professional and skilled maternal care givers is available to women. The WHSMP infrastructure and equipment should be fully operationalized to benefit greater number of women.